Assessing Technical Candidates on the Social Web - Capiluppi, A.; Serebrenik, A.; Singer, L. (IEEE software, 2013)
The Social Web provides comprehensive and publicly available information about software developers, identifying them as contributors to open source projects, experts at maintaining ties on social network sites, or active participants on knowledge-sharing sites. These signals, when aggregated and summarized, could be used to define potential candidates' individual profiles: potential employers could qualitatively evaluate job seekers, even those lacking a formal degree or changing their career path, by assessing candidates' online contributions. At the same time, developers are aware of the Web's public nature and the possible uses of published information when they determine what to share with the world. Some might even try to manipulate public signals of technical qualifications, soft skills, and reputation in their favor. Assessing candidates on the Web for technical positions presents challenges to recruiters, the most serious being the interpretation of the provided signals. An in-depth discussion proposes guidelines for software engineers and recruiters to help recruiters interpret the value and trouble with the signals and metrics they use to assess a candidate's characteristics and skills.